A novel approach for performance assessment of mechanical draft wet cooling towers. (5th July 2017) - Naik, B. Kiran; Muthukumar, P.
Highlights: Simple analytical model for cross-flow cooling tower is proposed. Predicted performances of the cooling tower match well with the experimental data. Analyzed the performances of the cooling tower for humid subtropical climate. Effects of various operating parameters on cooling tower performances are studied. Developed model provides useful guidelines for the preliminary design purposes. Abstract: Wet cooling tower is one of the key components of large scale water cooled air conditioning plants, whose efficiency influence the COP of the plant to a large extent. This study proposes a simple analytical model for calculating the amount of water taken up by the ambient air in a cross-flow wet cooling tower. An expression is derived using the condenser and the cooling tower effectiveness, to estimate the water evaporation loss of the cooling tower in terms of known inlet parameters. The model predictions are compared with experimental data and good agreement is observed. Also, good agreement exists between the predictions from the analytical model and experimental findings available in the literature. The influence of operating parameters such as water inlet temperature, relative humidity, air dry bulb temperature and specific humidity on the evaporation loss, heat load and tower efficiency are investigated for a humid subtropical climate. The results show that the above listed operating parameters, except air dry bulb temperature have a significant impact on the performance of the cooling tower. Furthermore, influences of refrigerant inlet temperature, thermal effectiveness of the cooling tower and condenser effectiveness on the performance of the wet cooling tower are also investigated.